2023
DOI: 10.1186/s13058-023-01603-w
|View full text |Cite|
|
Sign up to set email alerts
|

Multimorbidity and overall survival among women with breast cancer: results from the South African Breast Cancer and HIV Outcomes Study

Abstract: Background Breast cancer survival in South Africa is low, but when diagnosed with breast cancer, many women in South Africa also have other chronic conditions. We investigated the impact of multimorbidity (≥ 2 other chronic conditions) on overall survival among women with breast cancer in South Africa. Methods Between 1 July 2015 and 31 December 2019, we enrolled women newly diagnosed with breast cancer at six public hospitals participating in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Major findings were that the cohort had a high burden of HIV and common noncommunicable diseases, which results in frailty, necessitating less aggressive treatment approaches [ 27 , 28 ], poorer responses to neoadjuvant chemotherapy and negatively impacts overall survival [ 17 , 21 , 27 ]. The sites differed in age and ethnicity distributions of patients managed and had differing pathways for patients to access diagnostic and cancer treatment centres.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Major findings were that the cohort had a high burden of HIV and common noncommunicable diseases, which results in frailty, necessitating less aggressive treatment approaches [ 27 , 28 ], poorer responses to neoadjuvant chemotherapy and negatively impacts overall survival [ 17 , 21 , 27 ]. The sites differed in age and ethnicity distributions of patients managed and had differing pathways for patients to access diagnostic and cancer treatment centres.…”
Section: Discussionmentioning
confidence: 99%
“…Each participating hospital had dedicated study interviewers who collected sociodemographic characteristics, risk factors, comorbidities, and breast cancer clinical information knowledge and awareness of breast cancer and delay periods to diagnosis as previously described [ 6 , 17 ]. Some of the collected information and variables included the following: sociodemographic information (such as age, marital status, employment status, and level of education completed); behavioural factors (alcohol consumption, smoking); reproductive history (use of oral and injectable contraceptives, number of full-term pregnancies).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], the authors reported an error in the title. There is a break in the title and a large blank space besides the “background” section.…”
mentioning
confidence: 99%